2017
DOI: 10.1007/s40123-017-0101-y
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysical Measurements of Luminance Contrast Sensitivity and Color Discrimination with Transparent and Blue-Light Filter Intraocular Lenses

Abstract: IntroductionThe purpose of this study was to measure luminance contrast sensitivity and color vision thresholdfs in normal subjects using a blue light filter lens and transparent intraocular lens material.MethodsMonocular luminance grating contrast sensitivity was measured with Psycho for Windows (version 2.36; Cambridge Research Systems) at 3.0, 6.0, 12.0, 20.0, and 30.0 cycles per degree of visual angle (cpd) in 15 normal subjects (eight female), with a mean age of 21.6 years (SD = 3.8 years). Chromatic disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…However, no observable hue perception trend across the entire colour spectrum has been reported. In the present study, to avoid the effects of blue light-filtering IOL on perception along the blue-yellow axis or sensitivity to blue light spectrum under mesopic light condition [32, 42], we recruited patients implanted with UV light-filtering IOL in the patient group. PES analyses on the FM circuit revealed that postoperative photopic hue discrimination changes were most prominent in yellow, greenish yellow, yellow green, yellowish green, green and bluish green surface colours, which broadened to include greenish blue under mesopic condition.…”
Section: Discussionmentioning
confidence: 99%
“…However, no observable hue perception trend across the entire colour spectrum has been reported. In the present study, to avoid the effects of blue light-filtering IOL on perception along the blue-yellow axis or sensitivity to blue light spectrum under mesopic light condition [32, 42], we recruited patients implanted with UV light-filtering IOL in the patient group. PES analyses on the FM circuit revealed that postoperative photopic hue discrimination changes were most prominent in yellow, greenish yellow, yellow green, yellowish green, green and bluish green surface colours, which broadened to include greenish blue under mesopic condition.…”
Section: Discussionmentioning
confidence: 99%
“…Cataract surgery involving the implantation of clear IOLs has increased light transmittance at approximately 410 nm that might be associated with the risk of age-related macular degeneration [14]. To minimize this, yellow-tinted IOLs that absorb blue light are available [3,[14][15][16][17][18][19].…”
Section: Iolsmentioning
confidence: 99%
“…Cataract surgery involving the implantation of clear IOLs has increased light transmittance at approximately 410 nm that might be associated with the risk of age-related macular degeneration [ 14 ]. To minimize this, yellow-tinted IOLs that absorb blue light are available [ 3 , 14 , 15 , 16 , 17 , 18 , 19 ]. A bulky haptic, such as those of the foldable one-piece IOLs can hamper capsular bend formation and adhesion [ 13 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The subjective impression showed in all participants a better color vision under blue light filter condition. To summarize, no quantitative differences were found in the luminance sensitive between both types of lenses, although the blue light filter was reported to be more comfortable than the transparent filter 23 .…”
Section: Discussionmentioning
confidence: 75%